FILLMORE'S CASE GRAMMAR ANALYSIS OF 'JINNIYAT JABAL KUMANG' FILM DIALOGUES - Abdul Basid; Neng Sumiyati; Nadya Nafisah; Ely Fauziyah (Leksema: Jurnal Bahasa dan Sastra, 2022)
This study aimed to describe the modalities and propositions in the dialogues of the film entitled Jinniyāt Jabal Kumang based on case grammar theory from Charles J. Fillmore. This is a literary research that applied descriptive-qualitative method. The result of this study showed that from the dialogues there were found three types of time modalities, namely past, present and future; two forms of adverbial modality, i.e.: quantitative and frequency; an a negation modality. Meanwhile, the types of propositions found were the agentive, objective, source, goal, instrument, time, accompanying, benefactive, and locative cases. From the findings, it can be concluded that the case grammar analysis is applicable to Arabic sentence structure similar that of English and Indonesian language.